The Guiding Principles of the profession. A comparative study of Ethical Codes promoted by PR associations - Ruiz-Mora, Isabel María; Goncalves, Gisela; Miquel-Segarra, Susana (My University, 2021)
Ethics has been central to the debate about what public relations is, what it does and how it should be practiced in contemporary times. Ethical codes are a moral reference regarding the duties and rights of a profession. In this paper we reflect about the main values that guide PR practice based on Schwartz’s theory of basic human values, which measures universal values that are recognized throughout all major cultures. We aim to ascertain which basic human values are portrayed on the codes of public relations associations worldwide and understand their similarities/discrepancies with the global code of ethics portrayed by the Global Alliance. A qualitative and quantitative content analysis was carried out of the codes of ethics of six national PR and communication associations (representative of the sector in Europe and Americas) and of the Global Alliance's code as an international reference institution. The codes analysed were DIRCOM, Spain; ABERJE, Brazil; APCE, Portugal; CIPR, the United Kingdom; CPRPA, Argentina; PRSA, United States; and the Global Alliance. The documents obtained were analysed according to Schwartz's "Theory of the Universal Structure of Human Values" (1999) to study the priorities of values contained in the ethical codes of the public relations associations analysed, and to highlight the motivational values that may be present in them. The researchers adapted the codes to the structure, based on the descriptions of Schwartz's typology of values, and classified them according to higher-order types and their dimensions.
Keywords: Ética profesional; Asociaciones profesionales; Ethic; Public Relations; Professional Associations; Ethical Codes; Principles; Theory of the Universal Structure of Human Values